2023
DOI: 10.1002/ptr.7799
|View full text |Cite
|
Sign up to set email alerts
|

Xanthohumol inhibits non‐small cell lung cancer via directly targeting T‐lymphokine‐activated killer cell‐originated protein kinase

Abstract: Xanthohumol is a principal prenylated chalcone isolated from hops. Previous studies have shown that xanthohumol was effective against various types of cancer, but the mechanisms, especially the direct targets for xanthohumol to exert an anticancer effect, remain elusive. Overexpression of T-lymphokine-activated killer celloriginated protein kinase (TOPK) promotes tumorigenesis, invasion and metastasis, implying the likely potential for targeting TOPK in cancer prevention and treatment.In the present study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Immunohistochemical staining showed in vivo reduced expression of Ki-67, cyclin D1, and Fra1 with concurrent upregulation of the proapoptotic protein PUMA. All of the aforementioned results demonstrate the potential of XH as an anti-tumor agent for the management of lung cancer [ 170 , 171 , 177 ].…”
Section: Chalcones and Lung Cancermentioning
confidence: 98%
See 1 more Smart Citation
“…Immunohistochemical staining showed in vivo reduced expression of Ki-67, cyclin D1, and Fra1 with concurrent upregulation of the proapoptotic protein PUMA. All of the aforementioned results demonstrate the potential of XH as an anti-tumor agent for the management of lung cancer [ 170 , 171 , 177 ].…”
Section: Chalcones and Lung Cancermentioning
confidence: 98%
“…Treatment with XH significantly reduced the phosphorylation of TOPK as well as its downstream signaling molecules Akt and histone H3 in A549 and HCC827 cells and also suppressed its kinase activity. Biomolecular interaction analysis showed that this effect is mediated by direct interaction between XH and TOPK [ 177 ]. The targets of XH also include topoisomerases, enzymes essential for DNA relaxation during replication, transcription, mitosis, and other processes.…”
Section: Chalcones and Lung Cancermentioning
confidence: 99%